2014
DOI: 10.1364/boe.5.002870
|View full text |Cite
|
Sign up to set email alerts
|

Dermascope guided multiple reference optical coherence tomography

Abstract: Abstract:In this paper, we report the feasibility of integrating a novel low cost optical coherence tomography (OCT) system with a dermascope for point-of-care applications. The proposed OCT system is based on an enhanced time-domain optical coherence tomographic system, called multiple reference OCT (MR-OCT), which uses a single miniature voice coil actuator and a partial mirror for extending the axial scan range. The system can simultaneously register both the superficial dermascope image and the depth-resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In previous studies, additional use of OCT to dermoscopy showed improvement of sensitivity and specificity in diagnosing non-pigmented BCC [27] and provided more precise presurgical margin of BCC [28]. Recently, a technical combination of dermoscopy and OCT using a dichroic mirror (DM) was demonstrated [29]. However, it did not utilize augmented functional OCT techniques such as polarization-sensitive and angiographic OCTs.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, additional use of OCT to dermoscopy showed improvement of sensitivity and specificity in diagnosing non-pigmented BCC [27] and provided more precise presurgical margin of BCC [28]. Recently, a technical combination of dermoscopy and OCT using a dichroic mirror (DM) was demonstrated [29]. However, it did not utilize augmented functional OCT techniques such as polarization-sensitive and angiographic OCTs.…”
Section: Introductionmentioning
confidence: 99%
“…A simple experiment, which is commonly performed for the calibration of MR-OCT systems, is done by acquiring A-lines of a single-reflecting surface (such as a mirror or optical blank) and stepping it toward or away from the system with successive scans. 7 If all of the processing steps outlined above are employed correctly, the resultant image is a clean, straight line. An example of the calibration of the miniature MR-OCT module used in this work can be seen in Fig.…”
Section: Multiple Reference Optical Coherence Tomography Processingmentioning
confidence: 99%
“…Dsouza et al have previously shown that the sensitivity of a benchtop MR-OCT falls off linearly (in dB) at a rate of 1.1 dB per order. 7 The primary explanation for this is that the reference intensity for each order decreases as a function of the transmission percentage of the partial mirror, i.e., a higher transmission value of the partial mirror will cause the intensity to fall off at a higher rate per order. However, the result shown in Fig.…”
Section: Multiple Reference Optical Coherence Tomography Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports demonstrated the development of a compact platform within a handheld low-coherence interferometry (LCI) system, 20 and a multiple reference (MR) OCT system. [21][22][23] The handheld LCI system used for in vivo ear imaging was based on a linear OCT approach, 20 and the overall cost to develop this system was significantly lower than most other FD-OCT systems. MR-OCT, another low-cost OCT approach, was developed based on a partial mirror and actuator configuration, generating a recirculating optical delay line.…”
Section: Introductionmentioning
confidence: 99%